2022
DOI: 10.3390/ijms23020739
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1a: Going beyond Traditional Use

Abstract: Glucagon-like peptide-1 (GLP-1) is a human incretin hormone derived from the proglucagon molecule. GLP-1 receptor agonists are frequently used to treat type 2 diabetes mellitus and obesity. However, the hormone affects the liver, pancreas, brain, fat cells, heart, and gastrointestinal tract. The objective of this study was to perform a systematic review on the use of GLP-1 other than in treating diabetes. PubMed, Cochrane, and Embase were searched, and the PRISMA guidelines were followed. Nineteen clinical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 103 publications
0
49
0
5
Order By: Relevance
“…Within the cardiovascular system, GLP-1 receptors are expressed on endothelial cells, monocytes, macrophages, and vascular smooth muscle cells (VSMCs) [ 9 ]. GLP-1 receptors are also widely expressed in the central nervous system, including the brainstem, cerebellum, hippocampus, cortex, hypothalamus, and amygdala [ 7 , 10 , 11 ]. There, the cellular expression of GLP-1 receptors is predominantly confined to neurons and dendrites [ 11 ].…”
Section: Glucagon-like Peptide-1 Receptor Agonists and Glucagon-like ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Within the cardiovascular system, GLP-1 receptors are expressed on endothelial cells, monocytes, macrophages, and vascular smooth muscle cells (VSMCs) [ 9 ]. GLP-1 receptors are also widely expressed in the central nervous system, including the brainstem, cerebellum, hippocampus, cortex, hypothalamus, and amygdala [ 7 , 10 , 11 ]. There, the cellular expression of GLP-1 receptors is predominantly confined to neurons and dendrites [ 11 ].…”
Section: Glucagon-like Peptide-1 Receptor Agonists and Glucagon-like ...mentioning
confidence: 99%
“…GLP-1RAs are overall well-tolerated, with their most common adverse effects being nausea, vomiting, and diarrhea [ 7 ]. It has been recently shown that there are cholecystokinin-expressing neurons in the caudal brainstem, which are activated postprandially and are responsive to GLP-1RAs, explaining in part the body weight-lowering effects of GLP-1RAs but also their ability to induce nausea [ 12 ].…”
Section: Glucagon-like Peptide-1 Receptor Agonists and Glucagon-like ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the direct effects on the cellular elements of the NVU, ancillary mechanisms of neuroprotection by GLP-1RAs may indirectly emanate from the attenuation of pathological processes in the periphery, in particular, favourable outcomes associated with GLP-1RAs on glucose and lipid metabolism, cardiovascular function and systemic inflammation [3,4,241]. As discussed above, the existing literature in animal models of Aβ amyloidosis and tauopathies indicates that the long-term activation of GLP-1 signalling attenuates protein aggregation in the brain (Table 2).…”
Section: Effects Of Glp1-ras In Periphery and Inter-organ Communicationmentioning
confidence: 99%
“…In a study of monocytes, metformin activated AMPK-induced mitophagy to restore normal mitochondrial function, thereby improving pancreatic beta cell function and IR ( Bhansali et al, 2020 ). Glucagon-like peptide-1 (GLP-1) receptor agonists can activate the GLP-1 receptor, enhance insulin secretion in a glucose-dependent manner, inhibit glucagon secretion, delay gastric emptying, and reduce food intake through central inhibition of appetite, thereby achieving hypoglycemic effects ( Laurindo et al, 2022 ). Liraglutide, an important GLP-1 receptor agonist, may play a key role in maintaining mitochondrial homeostasis by regulating PINK1/Parkin-mediated mitophagy and inhibiting PINK1/Parkin overexpression ( Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%